Structure, Stability, and Reorganization of 0.5 L0 Topography in Block Copolymer Thin Films - Maher, Michael J; Self, Jeffrey L; Stasiak, Pawel; Blachut, Gregory; Ellison, Christopher J; Matsen, Mark W; Bates, Christopher M; Willson, C Grant (ACS nano, 2016)
The structure, stability, and reorganization of lamella-forming block copolymer thin film surface topography ("islands" and "holes") were studied under boundary conditions driving the formation of 0.5 L0 thick structures at short thermal annealing times. Self-consistent field theory predicts that the presence of one perfectly neutral surface renders 0.5 L0 topography thermodynamically stable relative to 1 L0 thick features, in agreement with previous experimental observations. The calculated through-film structures match cross-sectional scanning electron micrographs, collectively demonstrating the pinning of edge dislocations at the neutral surface. Remarkably, near-neutral surface compositions exhibit 0.5 L0 topography metastability upon extended thermal treatment, slowly transitioning to 1 L0 islands or holes as evidenced by optical and atomic force microscopy. Surface restructuring is rationalized by invoking commensurability effects imposed by slightly preferential surfaces. The results described herein clarify the impact of interfacial interactions on block copolymer self-assembly and solidify an understanding of 0.5 L0 topography, which is frequently used to determine neutral surface compositions of considerable importance to contemporary technological applications.The structure, stability, and reorganization of lamella-forming block copolymer thin film surface topography ("islands" and "holes") were studied under boundary conditions driving the formation of 0.5 L0 thick structures at short thermal annealing times. Self-consistent field theory predicts that the presence of one perfectly neutral surface renders 0.5 L0 topography thermodynamically stable relative to 1 L0 thick features, in agreement with previous experimental observations. The calculated through-film structures match cross-sectional scanning electron micrographs, collectively demonstrating the pinning of edge dislocations at the neutral surface. Remarkably, near-neutral surface compositions exhibit 0.5 L0 topography metastability upon extended thermal treatment, slowly transitioning to 1 L0 islands or holes as evidenced by optical and atomic force microscopy. Surface restructuring is rationalized by invoking commensurability effects imposed by slightly preferential surfaces. The results described herein clarify the impact of interfacial interactions on block copolymer self-assembly and solidify an understanding of 0.5 L0 topography, which is frequently used to determine neutral surface compositions of considerable importance to contemporary technological applications.